How to decide which patient-reported outcome measure to use? A practical guide for plastic surgeons. Issue 7 (July 2018) - Dobbs, Thomas D.; Hughes, Sarah; Mowbray, Nicholas; Hutchings, Hayley A.; Whitaker, Iain S.
Summary: The use of patient-reported outcome measures (PROMs) is increasing across all medical specialties, as their importance to patient care is validated. They are likely to play a particularly important role in plastic and reconstructive surgery where outcomes are often subjective, and the recent guidance from the Royal College of Surgeons of England advising their use in cosmetic surgery highlights this. To drive their routine use across our specialty, it is important that clinicians are capable of understanding the often complex and confusing language that surrounds their design and validation. In this article, we describe the process of PROM design and validation, and we attempt to 'demystify' the language used in the health outcome literature. We present the important steps that a well-designed PROM must go through and suggest a straightforward guide for selecting the most appropriate PROMs for use in clinical practice. We hope that this will encourage greater use of PROM data across plastic and reconstructive surgery and ultimately help improve outcomes for our patients.